Modelagem e levantamento GPR em estruturas de concreto com antena de 400 MHz - MATOS JUNIOR, Odinei da Silva (2019)
This study aims to gather knowledge on the responses of the computer modeling program Reflexw on a known environment and observe how best to use real resources to addressing problems related to civil engineering. The environment chosen are building structures and observation of wear using GPR (Ground Penetrating Solo). The work proposes the use of a 400 MHz antenna to observe the most common problems in a building construction, and compare with responses obtained with the GPR Reflexw software, to detect possible restrictions on withdrawals or the software itself.